2017
DOI: 10.1111/his.13400
|View full text |Cite
|
Sign up to set email alerts
|

A novel histological examination with dynamic three‐dimensional reconstruction from multiple immunohistochemically stained sections of a PD‐L1‐positive colon cancer

Abstract: We confirmed that PD-L1 was highly expressed in the invasive frontal region in 3D models of MSI-H colon cancer tissue. This method can be useful for accurately evaluating the localisation of immune checkpoint molecules.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 10 publications
0
19
0
Order By: Relevance
“…To detect collagen fibers in colonic tissues, Masson trichrome staining was performed, according to the previously described method [22]. e sections were deparaffinized and rehydrated with xylene and 100, 95, and 70% ethanol.…”
Section: Masson Trichrome Stainingmentioning
confidence: 99%
“…To detect collagen fibers in colonic tissues, Masson trichrome staining was performed, according to the previously described method [22]. e sections were deparaffinized and rehydrated with xylene and 100, 95, and 70% ethanol.…”
Section: Masson Trichrome Stainingmentioning
confidence: 99%
“…These advantages are crucial in the evaluation of PD-L1 expression. Compared to the 3D PD-L1 evaluation method developed by Korehisa et al [ 18 ], which was based on computer reconstruction of PD-L1 IHC image from serial thin sections, our method has the advantages of “true” 3D imaging and preserved tissue integrity after imaging for further pathological examinations. Compared to the method developed by Lee et al .…”
Section: Discussionmentioning
confidence: 99%
“…Some studies 1 5 , 15 17 have provided valuable 3D information on microscopic morphology or gene expression of different types of tumors, by reconstruction of a part of the tumor tissues from 75 to 500 serial slices using different systems. The entire tumor is hard to reconstruct completely at high resolution owing to a number of difficulties, such as, size limitations of slide scanner and microtome, poor uniformity/quality of serial whole-organ sectioning and staining, the time-consuming nature of the procedure, computer constraints, and limited software processing capability.…”
Section: Discussionmentioning
confidence: 99%
“…However, they do not yield a satisfactory resolution to distinguish the tumor mass from normal tissue. Several studies have reported 3D models of tumor architecture based on reconstruction of light microscopic image sections 1 5 , which show promise in cancer research. However, ultrahigh-resolution 3D reconstruction of the entire bulk of a tumor is not yet to be achieved.…”
Section: Introductionmentioning
confidence: 99%